Squaring up the health economics of PCSK9 monoclonal antibodies ‘down under’ - Watts, G.; Norman, Richard (Elsevier Ireland Ltd., 2018)
Seminal data from population genetics have presaged the development of several novel lipid-regulating drugs and the prospect of more effectively addressing high residual risk of cardiovascular disease (CVD) in patients receiving secondary prevention therapies [1]. The most impressive development is the identification of proprotein convertase subtilisin/kexin type 9 (PCSK9), a regulator of the intracellular cycling of the low-density lipoprotein (LDL) receptor, as a target for lowering LDL-cholesterol (LDL-C) [2]. This journey most recently entered the phase of large scale CV outcome trials [2]. The most widely tested method for inhibiting PCSK9 entails the use of humanized monoclonal antibodies (mAbs) [2]. However, their high acquisition costs and budgeting impact on healthcare are concerning [3].